Post occupancy evaluation model: adaptive measure towards sustainable neighborhood development - Yaman, Rostam; Thadaniti, Suwattana; Ahmad, Noraini; Abdullah, Jamalunlaili; Ismail, Farrah Zuhaira (Malaysian Institute of Planners, 2018)
Sustainable development is key to the strategic sustainability within a society. Sustainable neighbourhood development (SND) is a fundamental element of a sustainable community. However, SND on it own will certainly not permit all stakeholders, particularly the end-users, to efficiently address current or projected future issues that positioned beyond the extent of physical development scope. Thus, this research aims to explore whether pre-occupancy assessment criteria addresses the adaptive measures of sustainable dimension pillars (SDP) upon post-occupancy holistically. The research objective is to identify the post-occupancy sustainable criteria gap of SND. To achieve this, the research applied Stakeholders-Inclusion Approach using Post-Occupancy Evaluation Model (POEM) Handbook as measurement tool. This research seeks to measure and identify SDP gap on economic, social and environmental balance and responsive approach towards incremental improvements in SND at community and individual levels. The findings indicated that there are SDP adaptation gaps in post-occupied SND.